ON THE UNDERSTANDING OF AEOLIAN SEQUENCE STRATIGRAPHY: AN EXAMPLE FROM MIOCENE-PLIOCENE DEPOSITS IN PATAGONIA, ARGENTINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Upper Tertiary aeolian strata (Río Negro Formation) outcrop in extensive sea cliffs at the Northeast of Patagonia. These outcrops show deposits corresponding to a complete suite of aeolian and aeolian related sub-environments, and also provide excellent exposures to analyse the sedimentology and internal architecture from a sequence stratigraphic point of view. Field studies, supplemented withline-drawings of oblique photographs, allowed the recognition of seven aeolian depositional sequences within the succession, each one bounded by regional super surfaces (or deflation surfaces). Internally these aeolian sequences display a cyclic recurrence in facies, that yields a tentative genetic model for their evolution. As documented from field examples, each basic aeolian depositional sequence was deposited during a single aggradational period, and is bounded by unconformities related to degradational periods. Degradational periods are regional deflationary events, that resulted in deep-scoured to flat surfaces, characterised by erosion / non deposition in which the only recognised accumulation is isolated and large angular blocks of fine-grained aggregates, interpreted as residual remnants of deposits of the previous sequence. Aggradational periods are characterised by a near- continuous accumulations responsible for the sequence building. Differences in the aeolian sediment budget to the area and the rising rate of water table control the related facies types, and allow to discriminateearly and late aggradational sub-periods. Early aggradational sub-periods form under conditions of relatively fast rising water tables associated with moderate aeolian sediment budget, thus resulting in the development of extended wet interduneslaterally associated with aeolian dunes and dry interdunes. During late aggradational sub-periods, the depositional surface outdistanced the water table, and aeolian dunes and dry interdunes tend to predominate. This sub-period is also characterised by an upward tendency to stabilisation, evidenced by the common occurrence of palaeosols in upper levels. Although the preserved thickness of each aeolian sequence is closely related to the average subsidence rate, the internal facies evolution suggests an overall climatic control for their origin.